Targeted treatment of hypophosphatemia with trametinib in HRAS-related mosaic RASopathy - Mirza, Adil; Rossi, Corinne; Kulozik, Andreas; Banan, Rouzbeh; Sahm, Felix; Harrabi, Semi B.; Syrbe, Steffen; Choukair, Daniela (Orphanet journal of rare diseases, 2025)
Abstract - - Schimmelpenning-Feuerstein-Mims syndrome (SFMS) is a rare mosaic RASopathy associated with epidermal nevi, neurological abnormalities, and increased cancer risk. We report a 2-year-old girl with - HRAS - -related SFMS, aggressive orbital rhabdomyosarcoma (eRMS) and severe hypophosphatemic rickets resistant to standard therapies. Treatment with the MEK inhibitor trametinib improved phosphate regulation, reducing FGF23 levels, and led to rapid developmental progress, including independent walking. After 29 months, the patient remains in cancer remission with stable phosphate levels. This case highlights trametinib’s potential in managing complex manifestations in SFMS and suggests MEK inhibitors as promising for treating mosaic RASopathies.